Prognostic and predictive factors associated with ipilimumab-related adverse events: a retrospective analysis of 11 NCI-sponsored phase I clinical trials - Chauhan, Aman (Oncotarget, 2020)
Background: We review factors impacting ipilimumab-associated adverse events through the experience from National Cancer Institute (NCI)-sponsored phase I immunotherapy clinical trials. Materials and Methods: Attributable ipilimumab-related adverse events from NCI-sponsored phase I immunotherapy clinical trials were queried retrospectively by anonymized patient experience reports for observed adverse events like decreased hematological cell counts, blood electrolytes or proteins, or reduced patient performance status. The prevalence of ipilimumab-related toxicity was associated by patient to the duration of ipilimumab exposure, radiographic responses, progression-free survival, and overall survival. Results: 373 patients from 11 phase 1 ipilimumab clinical trials were analyzed. Patients experiencing at least one grade 3 or 4 adverse event associated with observed radiographic response were included. The average number of grade 3/4 adverse events in responders was 1.167 versus 0.645 in non-responders (p = 0.001). Patient performance status did not significantly impact observed toxicity grade. Pretherapy lymphocyte count or chemistries were not associated with ipilimumab-associated toxicity. The number of agents combined with ipilimumab on trial was associated with average number of grade 3/4 toxicities–ipilimumab monotherapy (0.631) versus ipilimumab + 1 agent (0.877) versus ipilimumab + 2 agents (1.408) (p = 0.014). Number of low grade (grade 1/2) toxicities was associated with duration of treatment, Pearson correlation coefficient r = 0.456 (p < 0.0001); whereas the number of high grade (grade 3/4) toxicities was not, r = 0.032 (p = 0.546). Conclusions: Ipilimumab-attributed grade 3/4 toxicity was associated with therapeutic response. The number of co-administered agents added to ipilimumab significantly raised the likelihood of toxicity. Extended duration of treatment increased the incidence of low but not high-grade toxicity.